Effect of pollen substitutes feeding on some activities of two honeybee races - Abd El Salam, A. L.; Eissa, I.S.; Yousef, A. D. M.; Mohamed, R. A. H. (2009)
the following study was designed to measure the effect on royal jelly, honey and pollen production, when honeybees were fed a pollen substitutes.
Includes reference.
Summary in Arabic.
1
Keywords: Honeybee -- Feeding and feeds; Bee pollen